Unveiling the Nexus between Priority Sectors Lending and Credit Risk - Prem Bahadur Budhathoki; Shiva Raj Ghimire; Yeak Narayan Shrama (Financial Markets, Institutions and Risks)
This study investigates how priority sector lending affects non-performing loans in Nepalese Banks. In addition, this current study examines the influence of capital adequacy ratio, credit-to-deposit ratio, interest rates, and net liquidity, on non-performing loans. This study employed secondary data sourced from the Nepal Rastra Bank covering the period from 2021Q2 to 2023Q4. The analysis utilizing ordinary least square, fixed effect, random effect, and fully modified ordinary least square, indicates that non-performing loans is positively and significantly influenced by priority sector lending, with consistent results across all regression models. In a similar manner, interest rate has a favorable influence on non-performing loans and demonstrates robustness across all regression models. Similarly, non-performing loans has been positively influenced by net liquidity and demonstrates strength in ordinary least square, fixed effect, and random effect models; however, while the sign remains consistent in the fully modified ordinary least square model, it lacks statistical significance. Non-performing loan has experienced negative impacts from both capital adequacy ratio and credit-to-deposit ratio. However, they do not produce consistent results across all regression models. This study demonstrates the need for government-backed guarantee funds to increase bank lending for priority sector to support the balanced economic development of this nation.